Diabetic ketoacidosis after the treatment of anaphylaxis. (18th August 2022) - Brenner, Daniel S; Kleinman, Keith; Manzo, Amy; Bembea, Melania M; Cooke, David W
Abstract : Summary: Anaphylaxis is a rapidly progressive potentially lethal condition, and epinephrine is the most crucial medication in its treatment. In this study, we present a case of diabetic ketoacidosis in a young woman that was precipitated by the administration of epinephrine to treat anaphylaxis. This patient had diabetes mellitus and poor glycemic control and developed ketoacidosis despite having evidence of ongoing endogenous insulin production and having been treated with exogenous long-acting insulin less than 24 h prior to the event. This is a rare, serious, adverse side effect of life-saving medication. This report demonstrates that the risk of diabetic ketoacidosis should be considered when administering epinephrine to patients with diabetes, even in the absence of complete insulin deficiency. Learning points: Epinephrine directly suppresses insulin secretion, stimulates lipolysis, and causes ketone body generation. High-dose catecholamine administration can cause unexpected diabetic ketoacidosis in patients with risk factors. Early administration of insulin may not protect patients from developing ketoacidosis in the setting of high-dose catecholamine administration.